ASSESSMENT OF THE DAMAGE CAUSED BY MELOIDOGYNE INCOGNITA ON OKRA (ABELMOSCHUS ESCULENTUS) - M. A. Hussain; T. Mukhtar; M. Z. Kayani (Journal of Animal and Plant Sciences, 2011)
Among the most damaging root-knot nematode species, Meloidogyne incognita is one of the major constraints to okra (Abelmoschus esculentus L.) in vegetable-growing areas in Pakistan and other countries of the world. The relationship between a geometric series of six initial population densities (Pi) of M. incognita per Kg of soil and growth parameters and nematodes infestations was investigated on okra. Observations were recorded 45 days after inoculation with the nematode. It was found that all the inoculum levels reduced the shoot and root lengths, and fresh and dry weights. Increasing the nematode inoculum level increased the number of galls, egg masses and nematode population build up. The reductions in growth parameters and nematode infestations were found to be directly proportional to the inoculum level. On the other hand an inverse relationship was observed between the nematode build up and inoculum levels.
Keywords: Meloidogyne incognita; inoculum densities; Abelmoschus esculentus